Pemikiran Tokoh Pendidikan Di Indonesia Kh. Hasyim Asy’ari: Tinjauan Dari Bimbingan Dan Konseling - Mosleh, Ikrimania; Nurmalahayati, Santi; Nursalim, Mochamad; Nuryono, Wiryo (Institut Agama Islam Negeri Padangsidimpuan, 2025)
This study aims to evaluate the thoughts of KH. Hasyim Asy'ari in the context of education in Indonesia, especially from the perspective of guidance and counseling. KH. Hasyim Asy'ari, the founder of the Tebuireng Islamic Boarding School, is a prominent Islamic scholar whose ideas have had a profound impact on the development of Islamic education in Indonesia. He emphasized the importance of integrating religious sciences with general knowledge, highlighting that education should not only aim to enhance students' intellectual capacity, but also focus on building character, spirituality, and moral values. One of the core ideas in his educational philosophy is the crucial role of educators as guides and role models who assist students not only in academic matters but also in facing life's broader challenges. From this perspective, the function of guidance and counseling becomes essential in implementing a holistic educational approach. Teachers are expected to take on a more personal and ethical role in supporting the overall development of their students. The research method used in this study is qualitative, utilizing a literature review approach. This includes the analysis of biographies, historical accounts of Islamic education, and scholarly works that relate to the relevance of KH. Hasyim Asy'ari’s educational principles in the field of guidance and counseling today.